2017
DOI: 10.7189/jogh.07.010419
|View full text |Cite
|
Sign up to set email alerts
|

Integrating palliative care into national health systems in Africa: a multi–country intervention study

Abstract: BackgroundThe WHO is calling for the integration of palliative care in all health care settings globally.MethodsA 3.5–year program was implemented in 12 government hospitals, three each in Kenya, Rwanda, Uganda and Zambia. A four–pillared approach of advocacy, staff training, service delivery strengthening and international and regional partnership working was utilized. A baseline assessment was undertaken to ascertain needs, and 27 indicators were agreed to guide and evaluate the intervention. Data were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 18 publications
(23 reference statements)
0
52
0
2
Order By: Relevance
“…The WHO Planning and Implementing Palliative Care services published research conducted by the University of Edinburgh and Makerere University in their Integrate project (funded by a Tropical Health Education Trust and the UK’s Department of International Development), which set out templates to show how these implementation strategies can be integrated into health systems. 5 6 …”
Section: Strategiesmentioning
confidence: 99%
“…The WHO Planning and Implementing Palliative Care services published research conducted by the University of Edinburgh and Makerere University in their Integrate project (funded by a Tropical Health Education Trust and the UK’s Department of International Development), which set out templates to show how these implementation strategies can be integrated into health systems. 5 6 …”
Section: Strategiesmentioning
confidence: 99%
“…Studies have shown that strengthening palliative care is a key component of strengthening healthcare systems more generally, as the impact of changing attitudes, skills and knowledge extends beyond that of palliative care itself [ 17 ]. The Sustainable Development Goals (SDGs) set out 17 goals and 168 targets to end extreme poverty, fight inequalities and injustice, and protect our planet by 2030 [ 18 ].…”
Section: The Need For Paediatric Palliative Carementioning
confidence: 99%
“…Since then the resolution has been used as an advocacy tool throughout the region to encourage member states to implement the resolution, ensuring that palliative care is ‘integrated’ within the health system. Emphasis has been put on the WHO building blocks for health systems strengthening [ 24 ], with the development of palliative care being recognised as a health systems strengthening approach, with examples being seen in various programmes, including the ‘ Integrate programme ’ in Uganda, Zambia, Kenya and Malawi [ 25 ]. Alongside this, there is a growing recognition of the need for Universal Health Coverage (UHC) – with palliative care being seen as an integral part of UHC.…”
Section: Key Conference Themesmentioning
confidence: 99%